2019
DOI: 10.1111/dpr.12355
|View full text |Cite
|
Sign up to set email alerts
|

Provision of basic services in slums: A review of the evidence on top‐down and bottom‐up approaches

Abstract: This article synthesizes the evidence on the effectiveness of top‐down and bottom‐up approaches in providing basic services in slums in developing countries. The findings indicate that: (1) government‐led top‐down approaches focus predominantly on connectivity, but approaches led by community‐based organizations (CBOs) and non‐government organizations (NGOs) improve many additional dimensions of access; (2) legal recognition of slums improves access to services in both approaches; and (3) NGO and CBO involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…How they would be safe? In many previous studies in India, it was well documented that there is a lack of availability, accessibility as well as inequality of these basic services and amenities in slum areas [ 44 , 45 ]. Thus, limited access to these services makes slum HHs more vulnerable to infectious diseases and most of the slum HHs are dependent on community toilets or water taps as well.…”
Section: Methodsmentioning
confidence: 99%
“…How they would be safe? In many previous studies in India, it was well documented that there is a lack of availability, accessibility as well as inequality of these basic services and amenities in slum areas [ 44 , 45 ]. Thus, limited access to these services makes slum HHs more vulnerable to infectious diseases and most of the slum HHs are dependent on community toilets or water taps as well.…”
Section: Methodsmentioning
confidence: 99%
“…For this to be addressed, the government needs a bottom-up approach to ensure the unreliability and inadequacy of water supply systems are solved in the slum areas. (Elayaraja, Devkar, Narayanan, & Annamalai, 2017). For example, Nairobi's fast-growing population puts strain on existing water supplies.…”
Section: The Provısıon Of Basıc Infrastural Servıce In Naırobı Slumsmentioning
confidence: 99%
“…Depending on the circumstances, they may be aid agencies and local employees who are sharing decisions through delegation and partnership (Rivas, 2015), or different aid agencies sharing information between themselves (Lotfi et al, 2016). A systematic review of providing basic services to slums found that national CEDIL methods working paper: Engaging Stakeholders with Evidence and Uncertainty: Developing a Toolkit cedilprogramme.org 40 government, NGOs and civil society organisations all had distinct contributions to make (Devkar et al, 2019).…”
Section: Engaging With Context-specific Evidence To Make Decisionsmentioning
confidence: 99%
“…However, for these circumstances (and others) the question remains 'which local stakeholders?' A systematic review of providing basic services to slums found that national government, NGOs and civil society organisations all had distinct contributions to make (Devkar et al, 2019).…”
Section: Appendix 1: Toolkit Developmentmentioning
confidence: 99%